CONSUMER DISPUTE RESOLUTION IN CROSS-BORDER ONLINE TRANSACTIONS THROUGH ALTERNATIVE DISPUTE RESOLUTION FROM THE PERSPECTIVE OF INTERNATIONAL LAW - Berlian, Cheny; Santoso, Mulia Akbar; Yuniarti, Rahmi; Hadi, M. Fikry (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2025)
The development of e-commerce has facilitated cross-border transactions but has also raised legal challenges in consumer dispute resolution. Differences in jurisdiction, limited accessibility, and the lack of international legal harmonization often make it difficult for consumers to seek justice. Alternative Dispute Resolution (ADR) has emerged as a practical solution that is faster and more cost-efficient compared to traditional litigation. This research aims to analyze the application of ADR in cross-border online transaction disputes and identify its challenges and opportunities from an international law perspective. Using a normative legal approach, this study examines international legal instruments such as the 1958 New York Convention and the UNCITRAL Model Law, as well as related domestic regulations. The results indicate that while ADR offers advantages in efficiency and accessibility, its implementation still faces barriers, including the lack of regulatory harmonization between countries, low consumer awareness, and limitations in Online Dispute Resolution (ODR) technology. To overcome these challenges, strengthening the international legal framework, educating consumers, and developing more inclusive ODR technology are necessary.